2021
DOI: 10.1097/qai.0000000000002635
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Outcomes for Heavily Treatment-Experienced Individuals Living With Human Immunodeficiency Virus in a European Cohort

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 30 publications
(40 reference statements)
3
28
0
Order By: Relevance
“…Overall, the prevalence of subjects with resistance at 2 or more classes (described as “heavily treatment-experienced patients” according to recent definitions) was 31%. [ 19 ] No patients had major mutations for DOR at baseline. However, a 50-year-old highly treated male (for whom DOR was combined with lenacapavir, dolutegravir, bDRV, and tenofovir alafenamide), showed the V108X mutation which causes a low-level reduction in susceptibility to DOR.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the prevalence of subjects with resistance at 2 or more classes (described as “heavily treatment-experienced patients” according to recent definitions) was 31%. [ 19 ] No patients had major mutations for DOR at baseline. However, a 50-year-old highly treated male (for whom DOR was combined with lenacapavir, dolutegravir, bDRV, and tenofovir alafenamide), showed the V108X mutation which causes a low-level reduction in susceptibility to DOR.…”
Section: Resultsmentioning
confidence: 99%
“…According to these criteria, 16.1% of the included PWH were classified as HTE. There is no general consensus on the definition of HTE PWH in the literature or guidelines, and multiple descriptions are available based on virologic failure and prior and current ART patterns and/or resistance data [ 2 , 6 , 13 , 14 ]. Previous studies in which the definition of HTE included consideration of resistance and/or prior exposure to ART have suggested that the prevalence of HTE PWH in the United States is <6% [ 6 , 13–15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A subset of PWH are heavily treatment-experienced (HTE), having experienced virologic failure on multiple different treatment regimens, and have limited remaining ART options because of multidrug resistance and intolerance to certain ART agents [ 1–5 ]. Treatment of HIV-1 in HTE PWH may be further complicated by factors such as advanced HIV disease with low CD4+ cell count (≤200 cells/mm 3 ), multiple comorbid medical conditions requiring concomitant medications, and treatment of or prophylaxis for opportunistic infections [ 1 , 2 , 5–7 ]. These individuals may be unable to achieve virologic suppression and are thus at risk of further disease progression and transmission of infection [ 1 ].…”
mentioning
confidence: 99%
“…A retrospective cohort study of commercial and Medicare Advantage health plan enrollees in the USA between 2013 and 2019 found that 16.1% of 14 258 people living with HIV were HTE [4]. An ongoing cohort study of 22 000 Europeans living with HIV estimates that approximately 10% are HTE, with this figure rising from just 5.8% in 2010 to 8.9% in 2016 [5]. Conversely, a study of ART-experienced individuals with HIV living in the USA found that the number with limited remaining treatment options declined from 5.2%-7.8% in 2000-2006 to <1% from 2012 through 2017 [6].…”
Section: Introductionmentioning
confidence: 99%